Strain-specific expression profiles of virulence genes in Helicobacter pylori during infection of gastric epithelial cells and granulocytes - Gieseler, Steffi; König, Brigitte; König, Wolfgang; Backert, Steffen (Microbes and Infection, 2005)
Helicobacter pylori expresses a variety of known virulence-associated factors, whose expression is likely to be dependent on the ecological niche of this pathogen. Here, we compared the temporal changes in the level of virulence-associated gene transcription in H. pylori strains isolated from patients with different pathology. Our aim was to study the coordinated gene expression profiles of these virulence factors during infection of AGS gastric epithelial cells and granulocytes. Using real-time quantitative (TaqMan) RT-PCR, we determined the mRNA expression of cagA, ureA, napA, katA, vacAs1 and vacAs2 alleles in a time course up to 6:h. The expression profiles of the investigated genes vary according to the strain, and were mainly either upregulated or unchanged upon bacterial contact with AGS cells. In contrast, upon contact with granulocytes, the majority of the genes were repressed in H. pylori. The following major results were obtained: (i) genetically diverse H. pylori exhibit different mRNA expression profiles, (ii) the expression patterns were strain-specific and time-dependent and (iii) the regulation of expression profiles was host cell dependent. These data were statistically significant and suggest that contact with target cells leads to an active cross-talk between the pathogen and its host. The use of Taqman-PCR to analyse the expression of mRNA of a bacterial pathogen in response to a changing host environment enabled us to identify variable and strain-specific transcription profiles in a sensitive and reproducible manner. © 2005 Elsevier SAS. All rights reserved.
Created from Fastlane, Scopus look-up
Keywords: Molecular pathogenesis; Pathogenicity island; Type IV secretion; Virulence